2021
DOI: 10.1055/s-0041-1730456
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ear, Nose and Throat Manifestations in COVID-19 Patients

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has dramatically spread all over the world, crossing the borders of all countries. It is presented mainly by lower respiratory tract symptoms such as fever, cough, dyspnea, and chest tightness. However, COVID-19 causes different upper respiratory tract-related symptoms including nasal congestion, sore throat, and olfactory dysfunction. Objective To discuss different ear, nose and throat (ENT) manifestations in COVID-19-positive patients and their relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…The relation between anosmia-dysgeusia and sex was statistically significant (p <0.05), while the rest of ENT manifestations were not statistically significant with sex. El-Anwar et al [17] from Egypt reported in their study, that the most frequently ENT manifestations were sore throat in (30%) patients, nasal congestion in (28.3%) patients, nasal obstruction in (26.7%) patients, sneezing in (26.6%) patients, headache in (25%) patients, olfactory and taste dysfunction in (25%) patients, and runny nose or rhinorrhea in (20%) patients. Srivastava et al [18] mentioned that the majority (66.5%) of the cases had sore throat, followed by cases of nasal congestion (54.1%).…”
Section: Resultsmentioning
confidence: 94%
“…The relation between anosmia-dysgeusia and sex was statistically significant (p <0.05), while the rest of ENT manifestations were not statistically significant with sex. El-Anwar et al [17] from Egypt reported in their study, that the most frequently ENT manifestations were sore throat in (30%) patients, nasal congestion in (28.3%) patients, nasal obstruction in (26.7%) patients, sneezing in (26.6%) patients, headache in (25%) patients, olfactory and taste dysfunction in (25%) patients, and runny nose or rhinorrhea in (20%) patients. Srivastava et al [18] mentioned that the majority (66.5%) of the cases had sore throat, followed by cases of nasal congestion (54.1%).…”
Section: Resultsmentioning
confidence: 94%
“…The COVIDENGUE scores were developed using MLR [ 9 ] which is the gold standard method for assessing non-ordered polytomous categorical outcomes [ 27 , 28 ]. Except for active smoking whose protective effect against SARS-CoV-2 infection remains a matter of debate among researchers [ 29 , 30 ], all predictors retained to build the scores had been previously identified as relevant indicators of COVID-19 or dengue or associated with OFIs (especially respiratory infections) [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ] This ensures both the validity of content of this scoring system and the possibility of contrasted predictions. For example, international travel had been identified as a source of COVID-19 during the first pandemic wave [ [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging often indicates air-fluid levels or fluid accumulation ( Figure 5 D). After the possibility of coronavirus disease 2019 (COVID-19) is ruled out by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RT-PCR test—because the clinical manifestations of rhinosinusitis are similar to the symptoms of COVID-19 [ 23 ] and patients recover from the illness by conservative ENT treatment—they can still receive a maxillary implant with or without a sinus lift.…”
Section: Common Maxillary Sinus Pathologies Before Maxillary Implanta...mentioning
confidence: 99%